2017
DOI: 10.1038/ijo.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, leptin and insulin in breast milk: associations with maternal characteristics and infant body composition in the first year of life

Abstract: Breast milk hormone concentrations were associated with several fixed and modifiable maternal characteristics. Higher concentrations of leptin and intermediate concentrations of insulin were associated with lower infant WFL in the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
117
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 47 publications
14
117
3
6
Order By: Relevance
“…Other studies that have reported no association between maternal BMI and milk adiponectin levels had lower precision of estimates because of fewer women with elevated BMI, self-reported maternal weights, and wide infant age ranges for milk sampling (14,17,18). Our results of a diminished association over time supports findings by Chan et al (16), who reported no association between maternal prepregnancy BMI and adiponectin levels in breast milk at 3 to 4 months post partum. The finding points out the importance of timing of milk collection.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Other studies that have reported no association between maternal BMI and milk adiponectin levels had lower precision of estimates because of fewer women with elevated BMI, self-reported maternal weights, and wide infant age ranges for milk sampling (14,17,18). Our results of a diminished association over time supports findings by Chan et al (16), who reported no association between maternal prepregnancy BMI and adiponectin levels in breast milk at 3 to 4 months post partum. The finding points out the importance of timing of milk collection.…”
Section: Discussionsupporting
confidence: 83%
“…In line with this hypothesis, we and others have demonstrated positive associations between milk leptin levels and maternal BMI , but findings on the relationship of maternal BMI to milk insulin and adiponectin have been less consistent. One factor that may explain disparate findings is that while milk composition is known to change over the course of lactation, with a general finding of declines in milk peptides over lactation , the current literature is characterized by within‐ and between‐study heterogeneity in the timing of milk sample collection for analysis . Furthermore, studies of milk hormone variation to date have not taken account of maternal metabolic status at different critical developmental windows.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…Chan et al . recently reported a U‐shaped relationship between HM insulin and infant WLZ in a large cross‐sectional study . Our data were longitudinal, included body fat measures and milk sampling controlled for maternal prandial state, which may have contributed to our detection of a more complicated relationship.…”
Section: Discussionmentioning
confidence: 95%